Pregnancy Intention Screening: Changes in Staff Perceptions With Training [8K]. (May 2018) - Jackson, Ashaki; Saleeby, Erin; Pietersz, Judith Dannelle; Zapata, Carmen; Thiel de Bocanegra, Heike
Abstract : INTRODUCTION: Integrating reproductive life preference (RLP) screening is part of a larger initiative to improve reproductive and sexual healthcare throughout the Los Angeles County Department of Health Services (LACDHS). The LACDHS implemented RLP training among clinic staff and evaluated impact of training on staff perceptions of the RLP questions and their incorporation into routine clinical care. METHODS: We collected pre- and post-survey data from training participants from April 2017 to September 2017. Survey items included RLP question knowledge, implementation confidence and attitudes on the importance of reproductive health. We analyzed changes with pre- and post-tests. RESULTS: A total of 175 medical staff—largely certified medical assistants (48.6%) and nurses (29.1%)—completed evaluation surveys. Analyses conducted on responses from staff who were already somewhat familiar with RLP questions revealed that by post-survey, staff more often perceived fewer barriers to implementing RLP questions in clinical settings, t(87)=3.34, P =.001; saw inclusion of RLP questions as helpful to their work, t(88)=−3.45, P =.001; and perceived the questions as helpful to information-gathering and the decision-making process, t(88)=−6.40, P =.001. Staff who were unfamiliar with RLP questions more often agreed that RLP questions improved the decision-making process and were useful to information-gathering at post-survey, t(75)=−2.37, P =.02. CONCLUSION: Training demonstrated some impact on perceptions of RLP question's value. Future research will include how often staff ask questions prior to and following training to clarify if training also impacts practice.